Pengaruh Pemahaman Mahasiswa Terhadap Penggunaan Jasa Keuangan Syariah Bank Dan Non-Bank (Studi Kasus Pada Mahasiswa STIES Indonesia Purwakarta) - Ratnasari Ratnasari; Ai Siti Khoeriah; Saepul Bahri (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
The third National Financial Literacy and Inclusion Survey (SNLIK) conducted by the Financial Services Authority (OJK) in 2019 showed the financial literacy index reached 38.03%. This figure is an increase compared to the results of the 2016 OJK Survey, namely the financial literacy index of 29.7%. Thus in the last 3 years there has been an increase in public financial understanding (literacy) by 8.33%, the 2019 SNLIK also noted that the level of Islamic financial literacy rose slightly from 8.1% to 8.93%. Completing the survey conducted by the OJK, the 2019 Islamic Economic Literacy Index issued by BI reached 16.3% (well literate) out of a 100% scale which reflects the space for efforts to increase public understanding of Islamic Economics in the country. This study aims to determine the effect of student understanding on the use of Islamic banking and non-bank financial services. The method used in this research is descriptive quantitative research method. The results of this study are the results of testing the validity of the understanding variable, it is known that rcount > rtable (0.213) with a significance value (p value) < 0.05 so that the understanding variable data is declared valid. Furthermore, the variable for the use of bank services obtained rcount > rtable (0.213) with a significance value (p value) <0.05 so that all statement items are declared valid. Next, it is known that the tcount is 5.417 > ttable (1.9904), with a probability value of 0.000 which means it is smaller than 0.05, then Ha is accepted, meaning that student understanding has a significant positive effect on the use of Islamic banking and non-bank financial services. And obtained a coefficient of determination (R Square) of 0.271, meaning that 27.1% of student understanding is able to explain or influence the use of Islamic banking and non-bank financial services, while the remaining 72.9% is influenced by other factors not examined in this study.